Dampak Persepsi Konsumen Terhadap Kualitas Layanan Di Bacarito Kopi - Maidawati; M.Olan Ayji; Riri Nasirly (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2025)
This research is motivated by the problem of unstable sales every year in Bacarito Kopi Padang. This is due to the inadequate quality of service, including parking that is not too wide and less regular as well as the service of some baristas who are less friendly and less smiling. The purpose of the study to determine the quality of Service Bacarito coffee in improving consumer satisfaction by using the Servperf method. Proposed improvements that need to be improved and improved on Bacarito coffee using IPA method. There are two methods used, namely Servperf and IPA. The Data used is in the form of primary data, namely data from questionnaires that have been distributed to 100 respondents with alternative answers using a Likert scale. The results showed the quality of Service Bacarito coffee in improving consumer satisfaction by using the Servperf method of 0,89. This means that consumers have not been satisfied with the quality of service provided, it is characterized by Q ≤ 1 which is 0,89 < 1. The IPA method in the Cartesian diagram shows that 4 of the 24 attributes used for proposed improvements are in quadrant I. The main priority for proposed improvements is in the attributes regarding menu information that must be clear, employee politeness and friendliness, parking area security and procedures for complaining about problems. This research can provide recommendations for business actors in the food and beverage industry to improve and increase the quality of service to consumers.